Husbands' Plan to Participate in Birth Preparedness and Complication Readiness in Haramaya Health and Demographic Surveillance System Site, Eastern Ethiopia: A Community-Based Cross-Sectional Study - Sufian, Seada; Kure, Mohammed Abdurke; Dheresa, Merga; Debella, Adera; Balis, Bikila; Roba, Kedir Teji (Frontiers in Public Health, 2022)
Background: Partner involvement in maternal health services utilization remains a major public challenge in developing world. . Moreover, the husbands’ involvement during pregnancy helps their spouse to make timely decisions and avoid maternal delays, especially first and second delays. In developing countries like Ethiopia, although birth preparedness and complication readiness has been investigated, almost all previous researchers were focused on women participants. Therefore, we aimed to investigate factors associated with husband involvement in birth preparedness and complication readiness plan in Haramaya Health and Demographic Surveillance site, Eastern Ethiopia. Methods: A community-based cross-sectional study was conducted from March 1 to 30, 2020 among 630 men whose wives were pregnant in Haramaya Health and Demographic Surveillance (HDSS) site Eastern Ethiopia. Participants were approached through systematic sampling technique. Data were collected using a pre-tested structured questionnaire through a face-to-face interview, and entered into Epidata version 3.1 and analyzed using SPSS version 22 (IBM SPSS Statistics, 2013). The prevalence was reported by proportion with 95% Confidence Interval (CI) and summary measures. Predictors were assessed using a multivariable logistic regression analysis model and reported using adjusted odds ratio with 95% CI. Statistical significance was declared at p-value <0.05. Results: Overall, the prevalence of husbands who intend to participate in birth preparedness and complication readiness was 59.6% (95%CI (56 %, 64 %). Knowledge of birth preparedness and complication readiness [AOR) = 4.18, 95%CI (2.05, 8.51)], having knowledge on danger signs during labor and delivery [AOR= 3.19, 95 % CI: (1.52,6.71)], discussion on place of delivery [AOR= 6.84, 95% CI: 4.17, 11.22)], and made postpartum plan [AOR= 2.30, 95 % CI: 1.38,3.85)] were factors statistically associated with husband plan. Conclusions: Husbands’ participation in birth preparedness and complication readiness was relatively low in this study area. Therefore, all stakeholders should give due emphasis to male partners’ education on importance of early birth preparedness and complication readiness plan to reduce potential complication during labor and delivery. Keywords: Husband participation, birth preparedness, complication readiness, associated factor, Eastern Ethiopia.